The Roots of Utopia - Dubicki, Andrzej; Rekść, Magdalena; Sepkowski, Andrzej; Agnieszka Gralak (Myths and Stereotypes in the Collective Representations, 2019)
“Ideology” of utopia is an abstraction of the methaphoric system of beliefs, values and institutional relationship that characterize a particular culture or society; mythology is the body of traditional narratives that exemplifies and historicized ideology. Myths are stories drawn from history, that have acquired through usage over many generations a symbolizing function central to the culture of the society that produces them. The language of myth assimilates the peculiar and contingent phenomena of secular history to archetypal patterns of growth and decay, salvation and damnation, death and rebirth. So formulated myths support that by understanding and imaginatively reenacting the conflict resolution of the past, we can interpret and control the unresolved conflicts of the present. The belief in ideal (utopistic) worlds is one of the oldest and most enduring patterns in western civilization. The idea that human history is divinely ordained and will lead to a period of heavenly perfection on earth can be dated at least as far back as the early prophecies. The search for salvation on earth is an obviously important component of the quest from ancient to our times. Its obvious, that every nation experiences its own fears and hopes and every tries to habituate them. Every nation needs a vision of utopia.